Are We Accurately Evaluating Depression in Patients with Cancer? - Saracino, Rebecca M. (Psychol Assess, 2019)
Depression remains poorly managed in oncology, in part because of the difficulty of reliably screening and assessing for depression in the context of medical illness. Whether somatic items really skew the ability to identify “true” depression, or represent meaningful indicators of depression, remains to be determined. This study utilized item response theory (IRT) to compare the performance of traditional depression criteria with Endicott’s substitutive criteria (ESC; tearfulness or depressed appearance; social withdrawal; brooding; cannot be cheered up). The Patient Health Questionnaire (PHQ-9), ESC, and Center for Epidemiologic Studies Depression Scale (CES-D) were administered to 558 outpatients with cancer. IRT models were utilized to evaluate global and item fit for traditional PHQ-9 items compared to a modified version replacing the four somatic items with ESC. The modified PHQ-9 ESC scale was the best fit using a Partial Credit Model; model fit was improved after collapsing the middle two response categories and removing psychomotor agitation/retardation. This improved model showed satisfactory scale precision and internal consistency, and was free from differential item functioning for gender, age, and race. Concurrent and criterion validity were supported. Thus, as many have speculated, utilizing the ESC may result in more accurate identification of depressive symptoms in oncology. Depressed mood, anhedonia, and suicidal ideation retained their expected properties in the modified scale, indicating that the traditional underlying syndrome of depression likely remains the same, but the ESC may provide more specificity when assessing patients with cancer.